Updated long‐term outcomes and prognostic factors for patients with unresectable locally advanced pancreatic cancer treated with intraoperative radiotherapy at the Massachusetts General Hospital, 1978 to 2010. Issue 23 (4th September 2013) - Cai, Sophie; Hong, Theodore S.; Goldberg, Saveli I.; Fernandez‐del Castillo, Carlos; Thayer, Sarah P.; Ferrone, Cristina R.; Ryan, David P.; Blaszkowsky, Lawrence S.; Kwak, Eunice L.; Willett, Christopher G.; Lillemoe, Keith D.; Warshaw, Andrew L.; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND In the current study, the authors evaluated long‐term outcomes, intraoperative radiotherapy (IORT)‐related toxicity, and prognostic factors for overall survival (OS) among patients with unresectable locally advanced pancreatic cancer (LAPC) who received IORT as part of their treatment at the Massachusetts General Hospital (MGH). METHODS Medical records were reviewed for 194 consecutive patients with unresectable LAPC who were treated with IORT at MGH between 1978 and 2010. OS was calculated using the Kaplan‐Meier method. Prognostic factors were evaluated at the univariate level by the log‐rank test and at the multivariate level by the Cox proportional hazards model. Rates of disease progression and treatment toxicity were calculated. RESULTS The 1‐year, 2‐year, and 3‐year survival rates were 49%, 16%, and 6%, respectively. Six patients (3%) survived for > 5 years. The median OS was 12.0 months. Among 183 patients with known post‐IORT disease status, the 2‐year local progression‐free survival and distant metastasis‐free survival rates were 41% and 28%, respectively. On multivariate analysis, an IORT applicator diameter ≤ 8 cm (hazards ratio [HR], 0.51; 95% confidence interval [95% CI], 0.30‐0.84 [P = .009]), a Charlson age‐comorbidity index ≤ 3 (HR, 0.47; 95% CI, 0.31‐0.73 [P = .001]), and receipt of chemotherapy (HR, 0.46; 95% CI, 0.33‐0.66 [P < .001]) predicted improved OS. The median OS for patients with all 3 positive prognostic factors was 21.2 months. CONCLUSIONS Well‐selected patients with LAPC with small tumors and low Charlson age‐comorbidity indices can achieve good long‐term survival outcomes with a treatment regimen that incorporates chemotherapy and IORT. Cancer 2013;119:4196–4204. © 2013 American Cancer Society.